Managerial capabilities and generic business strategies in the wineries of the ’Cava’ protected designation of origin - Ferrer, Juan R. (Spanish Journal of Agricultural Research, 2021)
Aim of study: Cava is Spain’s largest wine exporter. However, in the last 20 years, the growth of exports from Cava protected designation of origin (PDO) wineries has been lower than that of other Spanish PDO wines, and Cava’s domestic market share has fallen. From the point of view of strategic management, it could be said that it seems that the wineries of the Cava PDO are losing their competitive advantage. It is therefore fundamental to perform an analysis of the wineries that maintain a better performance to understand the elements that give them a competitive advantage. In this article, to analyse competitive advantage, both management capabilities and Robinson and Pearce’s generic business strategies are studied. The objective is twofold; on the one hand, we pursue the level of the managerial capabilities in the wineries of Cava PDO, while on the other hand, we seek to know the influence of the managerial capabilities and the strategies as reflected in their business performance. Area of study: Spanish wineries of the Cava PDO. Material and methods: Sixty-six wineries were analyzed using the Mann-Whitney U Test and Bayesian regression to determine the relationship between the managerial capabilities, strategy, and business performance. Main results: The results show a lower level of managerial capabilities in Cava PDO wineries as compared with Rioja PDO wineries, a strong relationship between management capabilities and performance. Research highlights: These results are highly applicable since they show what resources and what strategies should be promoted to achieve a competitive advantage.